2008
DOI: 10.1016/j.hal.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and immune response of the blue mussel (Mytilus edulis L.) after an exposure to the harmful dinoflagellate Prorocentrum minimum

Abstract: The harmful dinoflagellate Prorocentrum minimum has different effects upon various species of grazing bivalves, and these effects also vary with life-history stage.Possible effects of this dinoflagellate upon mussels have not been reported; therefore, experiments exposing adult blue mussels, Mytilus edulis, to P. minimum were conducted. Mussels were exposed to cultures of toxic P. minimum or benign Rhodomonas sp. in glass aquaria. After a short period of acclimation, samples were collected on day 0 (before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 50 publications
4
60
0
2
Order By: Relevance
“…Hégaret et al (2009) suggested that presence of large amounts of bacteria and hemocytes in the intestinal lumena of R. philippinarum reflected a failed attempt of the immune system to suppress opportunistic bacterial pathogens. Furthermore, Galimany et al (2008b) observed that hemocytes engulfed bacteria by phagocytosis in the alimentary canal lumina of mussels exposed to P. minimum.…”
Section: Discussionmentioning
confidence: 99%
“…Hégaret et al (2009) suggested that presence of large amounts of bacteria and hemocytes in the intestinal lumena of R. philippinarum reflected a failed attempt of the immune system to suppress opportunistic bacterial pathogens. Furthermore, Galimany et al (2008b) observed that hemocytes engulfed bacteria by phagocytosis in the alimentary canal lumina of mussels exposed to P. minimum.…”
Section: Discussionmentioning
confidence: 99%
“…Hemocyte infiltration and granuloma in the tissues have also been observed in other bivalves, such as bay scallops A. irradians, Pacific oysters Crassostrea gigas, blue mussels Mytilus edulis and Manila clams R. philippinarum exposed to Prorocentrum spp. (Wikfors and Smolowitz, 1993;Pearce et al, 2005;Galimany et al, 2008a;Hégaret et al, 2009). Wikfors and Smolowitz (1993) also reported degeneration of the digestive gland and presence of hemocyte aggregates (granulomas) in several tissues of bay scallops exposed to P. minimum.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic effects of P. minimum have been demonstrated several times with scallop bioassays (Hégaret and Wikfors, 2005a;Galimany et al, 2008a), even though the toxic agent is not clearly identified at this time. The dinoflagellate P. minimum may produce some toxic compound responsible for epithelial cell necrosis (Grzebyk et al, 1997) generating hemocyte infiltration or aggregation to accomplish tissue repair or to isolate the tissues from the algal cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations